Economic advantages of welding in construction - Slupska Yu. S. (НТУ «ДП», 2024)
Modern welding technologies have become an integral part of the construction industry. They provide effective solutions for joining structures that require high reliability and speed of assembly. Welding allows for the creation of rigid, non-detachable connections, which are ideal for various construction projects, ranging from small structures to large-scale infrastructure facilities.
Keywords: welding in construction